Blockchain-enabled Peer-to-Peer energy trading. (September 2021) - Wongthongtham, Pornpit; Marrable, Daniel; Abu-Salih, Bilal; Liu, Xin; Morrison, Greg
Highlights: Blockchain use cases for Peer-to-Peer energy trading are reviewed from the trilemma perspective. A scalable, robust, and secure model is proposed to support energy trading. A trial case study is used to assess the proposed model in its trilemma view and its economic value. Abstract: The increasing amount of distributed power generation from rooftop solar panels allows new electricity markets to emerge in which prosumers and consumers can trade locally produced energy. The use of blockchain technology has increasingly emerged in energy markets and shows great potential to facilitate Peer-to-Peer energy trading. However, blockchain technology is still in its infancy meaning it is not yet being used to its' full potential. In this paper, blockchain technology for Peer-to-Peer energy trading and its implications are explored, especially in view of the 'trilemma': scalability, security, and decentralisation. Peer-to-Peer energy trading is the focus of this paper, which ultimately proposes a blockchain scalability solution. This solution is empirically modelled using data collected in a trial case study. The proposed solution increases scalability without compromising security and decentralisation when compared to base layer models.